Space-pixel digital steganography method using spatial filtering to extract secret message - Юдін, О. К.; Весельська, О.М. (Science-based technologies, 2018)
As a tool of information technology, a quantum-spatial-pixel-based method (MAP) for embedding secret information in digital images has been developed, which provides more, compared with existing methods, the bandwidth of the latent channel and simplifies the system of data extraction, due to the use of spatial filtration The developed method is based on the change in the intensity of the brightness of the digital image pixels in the color RGB model. The change of intensity is carried out according to the developed set of rules and conditions through which the secret information (message) is embedded into the spatial area of ​​the digital image used as a container. Also, in order to reduce the probability of uncovering the existence of a message, it is proposed to embed pixel-only messages that are at intersection points with various functions that are superimposed on a digital image. The results of the research of the developed method in the software environment for digital images of different classes.